Geosite Assessments at the Southern Part of Karangbolong Dome: New Insight to Geotourism Potential in Kebumen, Central Java, Indonesia - Fadlin; Gentur Waluyo; Yohanes Iwan; Nita Ariyanti; Nanda Ajeng Nurwantari (Journal of Geoscience, Engineering, Environment, and Technology, 2020)
Karangbolong is a morphological dome in Kebumen area, that has a high geological diversity and have a lot of tourism potential, but has not been developed optimally as a geotourism potential based on conservative and educative aspects, especially the existence of ancient volcano of Menganti the quite interesting from a geological point of view, so in this case an inventory of a geological diversity is required. This study aims to understand the geological conditions and conduct an assessment of the feasibility of geodiversity in ancient volcano complex of Menganti. The methodology for this research is a direct observation in the field based on the surface geological mapping, rock sampling for petrology study of rocks for supporting the quantitative assessment of genocide in the research area. The research area has 2 (two) landscape models, ie,ex-volcanic landscape, in this case occupying 95% of the research area and then the karst landscape, occupying 5% of the research area. Stratigraphy of the research area can be divided into 5 units from old to young, that is basaltic lava of Menganti, the pyroclastic flow of Menganti which is interfingering with andesitic lava of Karangduwur, andesite-basalt intrusion unit, and limestone of Agropeni. Based on field investigation, the research area has 27 geosite objects that can be developed as geotourism potential, covering 3 geomorphological sites, 7 lithology sites, 9 cave karst sites, 5 beach sites, and 2 waterfall sites. Based on the results of quantitative assessment of geosites in the research area with accessibility, state of preservation, scientific wort, and educational significance parameters, the research area has a geodiversity index from 19 until 24, in this case, the research area has good until very good grade to be developed as a geotourism potential base on educative and conservative, in order to improve the economic value of local communities. Keywords: Qualitative assessment, geodiversity, geotourism, paleo-volcano, Kebumen.